Study of Behavioral Architecture Application at Bin Baz Putra Islamic Boarding School Bantul - Septian Fadillah Rahman; Sri Suryani Yuprapti Winasih (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
The moral decline of the nation's children is the most important issue today, and one of the solutions to solve it is through character education according to Islamic teachings in Islamic boarding schools. The Bin Baz Putra Islamic Boarding School is one of the Islamic boarding schools located in Piyungan, Bantul, Yogyakarta Special Region. As an educational institution, Islamic boarding school should apply a behavioral architectural approach as the basis for designing Islamic boarding school. So the purpose of this study is to examine the application of behavioral architecture in Bin Baz Putra Islamic Boarding School which is carried out using descriptive qualitative research methods from literature sources related to Islamic religious education in Islamic boarding schools and behavioral architecture, as well as a source of observations to collect informative data from boarding school object. The focus of the research is focused on the qualitative assessment of the area and facilities of the Bin Baz Putra Islamic Boarding School against several principles of behavioral architecture according to Carol Simon Weisten and Thomas G. David who then concluded that the Bin Baz Putra Islamic Boarding School in Bantul is still lacking in the application of behavioral architecture aspects, especially in physical comfort. students where bedrooms and student classrooms are not large enough to accommodate the number of students total 40 people.